العمل الفني وفكرة الجمال - سويعد، قصاص Suwaied, Qassas (جامعة زيان عاشور الجلفة, 2017)
The idea of beauty and its connection to creativity is not the product of the present, but extends to the early philosophical thought and its first manifestations. There is no doubt that the attempt to introduce any aesthetic idea into the philosophical research department forces us to invoke our knowledge tools to deal with any cognitive problem that leads us to recognize the need to invoke the human aesthetic dictionary by addressing the giants of aesthetics, including Kant, Descartes, Hegel, Croce, Aristotle.
فكرة الجمال وارتباطها بالإبداع ليست وليدة الحاضر بل امتدت بواكير الفكر الفلسفي وتجلياته الأولى ومما لا شك فيه أن محاولة إدخال أية فكرة جمالية إلى دائرة البحث الفلسفي تفرض علينا استحضار أدواتنا المعرفية لنتعامل مع أي إشكال معرفي تعاملا موضوعيا، يقودنا إلى التسليم بضرورة استحضار القاموس الجمالي الإنساني، وهذا من خلال التطرق إلى عمالقة علم الجمال ومن بينهم كانط، ديكارت هيغل، كروتشه، أرسطو.
Keywords: علم الجمال -- فكرة الجمال -- العمل الفني -- الإبداع الفني -- الفكر الفلسفي